Barriers and Strategies in the Implementation of Virtual Learning Modalities Amid COVID-19 among Students in Nursing Schools at Sulu Province, Philippines - Mukattil, Nursidar; Pangandaman, Hamdoni (Universitas Airlangga, 2024)
Introduction: The COVID-19 pandemic prompted a significant shift toward virtual learning modalities in nursing education. However, this transition has been marked by various challenges, including faculty and student unfamiliarity with online platforms and the need to adapt curricula rapidly. The purpose of this study to examine the barriers and strategies in the implementation of virtual learning among students in nursing schools at sulu province, philippines during the COVID-19 pandemic. Methods: Quantitative research study with a focus on descriptive analysis was employed to collect and analyze data from 95 nursing students across three higher education institutions in the Sulu Province. A questionnaire was used to assess sociodemographic factors, technology usage, and barriers experienced during virtual learning. Data were analyzed using frequency, percentage, mean, and standard deviation. Results: The results revealed that most participants were between 19 and 20 years old, with a higher percentage of females. The majority of students reported owning and using various online technologies, including online videos, social media platforms, mobile apps, and email. Key barriers to virtual learning included the absence of face-to-face interaction, poor internet connectivity, limited technical support, restricted access to clinical simulations, and distracting home environments. Language barriers, technical jargon in learning materials, limited access to required software, insufficient opportunities for collaboration, and privacy and security concerns were also identified as barriers. Conclusion: The findings underscore the importance of implementing key strategies to enhance virtual learning modalities in nursing education. These strategies can significantly improve the quality and effectiveness of virtual learning in nursing education, especially in challenging contexts like the Sulu Province.